Analysis of methods common topical treatment of the generalized dermatoses in the delivery of the specialized health care in the profile "Dermatology" - M. M. Kokhan; A. V. Samtsov; YU. N. Perlamutrov; E. V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Results of sampling epidemiological investigation of patients with dermatologic diseases, which sought treatment in the specialized Russian outpatient facilities over two-month period, and assessments of approaches to treatment of patients with atopic dermatitis, psoriasis and eczema are presented. Data of 2991 individual registration cards, which were filled out by the dermatovenerologists providing primary specialized care to patients in outpatient facilities of Perm, Samara and St. Petersburg, was analyzed. It was observed that women were prevalent among patients with dermatoses, and most of women and men were of working age (82.2 and 89.2% corresponding). The nosological structure of appealability consists of 25.6% patients with dermatose, psoriasis (14.5%), eczema (13.4%), seborrhea and acne (8.6%), atopic dermatitis (5.8%), and pyodermatitis (3.2%). Using standardized indexes for assessment it was discovered that among applied outpatients 80% persons, presented with atopic dermatitis, and 50% persons, presented with psoriasis, had moderate and severe appearances of dermatoses. In therapy of patients with atopic dermatitis, psoriasis and eczema, specialists used widely standard system treatment - topic glucocorticosteroid agents for external care.